Perang Kemerdekaan Irlandia (1919-1921) - Muhammad Rafly Dwi Ryanto Thenny Soendayana; Yeni Kurniawati (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2022)
Article entitled “War Independence Ireland 1919-1921". by general study this discuss about war independence Irish based _ with the guerrilla strategy carried out society and elite his nationalism Study this use method study history that includes heuristics, criticis, interpretation, and historiography, which are also assisted by approach interdisciplinary that is with knowledge political for help in writing article Before happening war, there incident Dail. The first (First Dail) to be base in issue the independence manifesto for Ireland. So that bring up spirit independence for people Ireland and be reference they in step next for defeat English with a guerrilla strategy .War independence that's what happened not enough more three year, though belong to short however reality war independence Ireland this many take its toll, which in the end won by the people Ireland through his attempted guerrilla strategy for maximizing the resources they have , and through the Anglo - Irish agreement which made Ireland as nations free states , as well as existence regional difference between Ireland with Northern Ireland . Study this will take corner look how party Ireland use tactics guerrilla in complete the conflict, and see continuity with events previously became root problem England and Ireland up to the peak with be marked with negotiation Among Ireland and England for end war is going on. Then for deepen Theory learning history in high school in particular discuss about incident easter world war 1.Keywords: Independence, Guerrilla, Negotiations, Ireland